Piecing together terminology in bioarchaeology - Cruz, Cristina Barroso (2022)
Recent data has shown that there is a great diversity of vocabulary related with bioarchaeology and funerary archaeology employed both in technical and scientific documents produced in Portugal. This phenomenon reflects, the lack of an uniform criteria in the application of concepts reflecting the circumstances and scientific preferences of the author, and as such revealing the subjectivity associated with the gathering of on field information during archaeological work. The lack of a standard framework limits data interpretation, by restricting a systematic approach to the information gathered and, consequently, impairing the comparisons amongst bio-demographic and sociocultural main features of Past Populations. Identifying this problem and its consequences led to the work that is currently being developed and that comprises the standpoint of reference authors in this matter, considering their contribution and presenting a proposal for the definition of the selected concepts. This strategy intends to produce a uniform language to be adopted in technical reports. It’s our hope that this approach could lead to a better understanding of archaeological field reports, increasing their informative potential that could later feed a bioarchaeological database. Thus it is our aim, with the present communication, to present the first effort of an ongoing project, to establish a common standard of main concepts on bioarchaeology.